Effectiveness of Music Listening in Patients With Total Knee Replacement During CPM Rehabilitation. (January 2016) - Hsu, Chih-Chung; Chen, Wei-Ming; Chen, Su-Ru; Tseng, Yen-Ting; Lin, Pi-Chu
Aim: This study investigated the effects of music listening on the anxiety, heart rate variability (HRV), and joint range of motion (ROM) of patients undergoing continuous passive motion (CPM) after total knee replacement surgery. Method: An experimental design was used. Participants in the experimental group ( n = 49) listened to music from 10 min before receiving CPM until the end of the session (25 min in total) on the first and second day following surgery, whereas participants in the control group ( n = 42) did not listen to music but rested quietly in bed starting 10 min before and throughout CPM. Results: Compared with the control group, the experimental group exhibited significantly lower anxiety levels ( p < .05) and increased CPM angles ( p < .05) during treatment and increased active flexion ROM ( p < .05) upon discharge. The low-frequency (LF)/high-frequency (HF) power ratio, normalized LF HRV, and normalized HF HRV of the two groups differed significantly, indicating that the patients in the experimental group had greater parasympathetic activity compared with those in the control group. Conclusion: Music listening can effectively reduce patient anxiety and enhance the ROM of their joints during postoperative rehabilitation. Health-care practitioners should consider including music listening as a routine practice for postoperative rehabilitation following orthopedic surgery.